1978
DOI: 10.1042/cs0540047
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Inhibition of Prostaglandin Synthesis on the Natriuresis Induced by Saline Infusion in Man

Abstract: 1. The effect of oral administration of an inhibitor of prostaglandin synthetase, indomethacin, on the natriuresis induced by the infusion of sodium chloride (saline) was studied in 11 healthy volunteers. 2. The administration of indomethacin did not alter sodium excretion before saline infusion, but it resulted in a significant increase of the natriuresis after saline infusion. This increase was not accompanied by any change in post-infusion urine flow rate or free water reabsorption. 3. It is suggested that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
1
2

Year Published

1979
1979
1991
1991

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 19 publications
0
11
1
2
Order By: Relevance
“…Attempts to define the effect of prostaglandin release on the natriuresis of ECVE by inhibition of prostaglandin synthesis have been contradictory, with reports suggesting that inhibition of prostaglandin synthesis may be either antinatriuretic (Verberckmoes et al, 1976;Donker et al, 1976;Patak et al, 1975;Berg, 1977;Diising et aL, 1976), natriuretic (Kirschenbaum and Stein, 1977;Mountokalakis et al, 1978;Kirschenbaum and Stein, 1976), or fail to affect renal sodium handling (Bohan and Wesson, 1976;Bailie et al, 1976). In several studies, inferences regarding the role of indomethacin on renal sodium excretion were drawn by assessing the natriuretic response to furosemide before and after indomethacin administration (Patak et al, 1975;Bailie et al, 1976).…”
Section: ± 5 286±4mentioning
confidence: 99%
See 4 more Smart Citations
“…Attempts to define the effect of prostaglandin release on the natriuresis of ECVE by inhibition of prostaglandin synthesis have been contradictory, with reports suggesting that inhibition of prostaglandin synthesis may be either antinatriuretic (Verberckmoes et al, 1976;Donker et al, 1976;Patak et al, 1975;Berg, 1977;Diising et aL, 1976), natriuretic (Kirschenbaum and Stein, 1977;Mountokalakis et al, 1978;Kirschenbaum and Stein, 1976), or fail to affect renal sodium handling (Bohan and Wesson, 1976;Bailie et al, 1976). In several studies, inferences regarding the role of indomethacin on renal sodium excretion were drawn by assessing the natriuretic response to furosemide before and after indomethacin administration (Patak et al, 1975;Bailie et al, 1976).…”
Section: ± 5 286±4mentioning
confidence: 99%
“…Papanicolaou et al (1975) assessed renal venous PGE levels without determining renal sodium excretion simultaneously. Although Mountokalakis et aL (1978) demonstrated that indomethacin administration augmented the natriuretic response to saline administration, renal PGE was not determined. Furthermore, in both studies, acute ECVE was induced by the administration of an intravenous saline load which presumably altered plasma composition.…”
Section: ± 5 286±4mentioning
confidence: 99%
See 3 more Smart Citations